Música erudita & música popular: a concepção desses conceitos na Revista Brasileira de Música (1934-1945) - Aranha, Luis Fernando Panades [UNIFESP] (2019)
This paper has as an object the Brazilian Journal of Music, published between 1934 and 1945. This Journal was produced by National Music Institute in Rio de Janeiro, Brazil, the first college of music in this contry. Our goal is to analise how the words popular music and classical music was mobilized by the autors inside this journal.